Renal safety of Long-Term Non-steroidal Anti-inflammatory drugs use in patients with ankylosing spondylitis - Young-Eun Kim; Seo Young Park; Ji Sung Lee; You-Jung Ha; Sooyoung Yoo; Seok Kim; Soo Min Ahn; Seokchan Hong; Chang‑Keun Lee; Bin Yoo; Ji Seon Oh; Yong‑Gil Kim (Scientific Reports)
Abstract Objectives We investigate the renal safety of long-term non-steroidal anti-inflammatory drugs (NSAIDs) exposure in patients with ankylosing spondylitis (AS). Methods We analyzed electronic medical records from Asan Medical Center (AMC) and Seoul National University Bundang Hospital (SNUBH), including 1,618 and 995 AS patients, respectively, with over one year of follow-up and no pre-existing kidney disease (baseline eGFR ≥ 60). NSAID exposure was quantified using the medication possession rate (MPR), and its impact on estimated glomerular filtration rate (eGFR) changes was assessed using linear mixed-effects models. Two approaches were employed: a 1-year interval analysis assuming a stable effect over time without time interaction, and a 3-year interval analysis incorporating time interaction to evaluate cumulative NSAID effects and changes in the relationship with eGFR decline over time. Results In the analysis without time interaction, NSAID use was associated with a decline in annual eGFR, with patients having 100% NSAID use experiencing a decrease in eGFR (β, -0.7; 95% CI: -1.1 to -0.3) compared to those with no NSAID use. A meta-analysis showed that every 1% increase in NSAID MPR associate with eGFR decline (β, -0.007; 95% CI: -0.011 to -0.004). However, the time-interaction analysis found no significant cumulative eGFR decline across most time points, except at the 9-year follow-up in SNUBH (β, -5.1; 95% CI, -9.2 to -1.1) and 18-year follow-up in AMC (β, -8.9; 95% CI, -15.9 to -1.9). Conclusion This study demonstrates that while NSAID use may affect renal function in the short term, its long-term cumulative effects on renal impairment appear non-significant.